(D^2 -4DD^'+ 3D^'^2)z =0
Rewrite this equation in the next view:
"z_{xx}-4z_{xy}+3z_{yy}=0"
Now lead it to canonical view. To do this, let input new variables:
"\\begin{cases}\n\\eta=y+x\\\\\n\\xi= y+3x\\\\\n\\end{cases}"
So now we have:
"\\dfrac{\\partial z}{\\partial x}=\\dfrac{\\partial z}{\\partial \\eta}+3\\dfrac{\\partial z}{\\partial \\xi}"
"\\dfrac{\\partial z}{\\partial y}=\\dfrac{\\partial z}{\\partial \\eta}+\\dfrac{\\partial z}{\\partial \\xi}"
"\\dfrac{\\partial^2 z}{\\partial x^2}=(\\dfrac{\\partial z}{\\partial \\eta}+3\\dfrac{\\partial z}{\\partial \\xi})^2"
"\\dfrac{\\partial^2 z}{\\partial y^2}=(\\dfrac{\\partial z}{\\partial \\eta}+\\dfrac{\\partial z}{\\partial \\xi})^2"
"\\dfrac{\\partial^2 z}{\\partial x \\partial y}=\\dfrac{\\partial z^2}{\\partial \\eta^2}+4\\dfrac{\\partial^2 z}{\\partial \\xi \\partial\\eta} + 9\\dfrac{\\partial z^2}{\\partial \\xi^2}"
"z_{\\eta\\eta}+6z_{\\eta\\xi}+9z_{\\xi\\xi}-4(z_{\\eta\\eta}+4z_{\\eta\\xi} +9z_{\\xi\\xi})+3(z_{\\eta\\eta}+2z_{\\eta\\xi}+z_{\\xi\\xi})=0"
The canonical equation:
"6z_{\\xi\\xi}+z_{\\xi\\eta}=0"
"\\dfrac{\\partial}{\\partial \\xi}(6\\dfrac{\\partial z}{\\partial \\xi} + \\dfrac{\\partial z}{\\partial \\eta})=0"
"6\\dfrac{\\partial z}{\\partial \\xi} + \\dfrac{\\partial z}{\\partial \\eta}=C_1(\\eta)"
"\\dfrac{\\partial \\xi}{6} =\\partial \\eta=\\dfrac{\\partial z}{C_1(\\eta)}"
"z_1=\\int C_1(\\eta) d\\eta +C_2"
"z_2=C_1(y+x)*(y+3x)+C_3"
Comments
Leave a comment